Growth and the lost legitimacy of business organisation: time to abandon corporate law reform. Issue 2 (2nd July 2020) - Galanis, Michael
ABSTRACT: Business organisation still reflects and reproduces the dated idea of 'economic growth as progress' irrespective of its social hazards. Recalibrating the grounding of business organisation's legitimacy requires radical legal reform in order to accommodate the relegation of growth as a lower order objective. However, this article shows that the normative debate in corporate law scholarship is unable to resolve the legitimacy problem of business organisation and ultimately reflects and reproduces the ideal of 'growth as progress'. The problem is corporate law per se . Thus, the article argues that, even if these normative difficulties could be surpassed, instituting a new legitimacy for business organisation through corporate law reform - the conventional remedy - is, at best, practically impossible or, worse, harmful, because it is bound to follow conformist logic. Consequently, it is preferable to abandon corporate law reform completely and policy should focus instead on enabling the radical organisational practice already occurring in the social margin.